Polymer solar cells - Singh, Ram Prakash; Kushwaha, Omkar Singh (Journal of Materials Education, 2013)
It is a well known fact that the amount of solar energy impinging on the earth's surface in one hour is higher than the worldwide energy demand per year. Solar energy is the ultimate renewable zero emission energy source. Solar energy technology which is dominated by the crystalline silicon has not found widespread acceptance due to size, weight, aesthetics, cost and installation of solar panels. On the other hand, polymer solar cells being light weight, inexpensive, colorful and capable to be fabricated into large area flexible devices by roll to roll processes, portend potential for large scale non-grid and grid power generation applications. Polymer solar cells would reduce the need for petroleum and natural gas for power generation; therefore, the use of cells would slow down the disappearance of non-renewable resources and promote sustainability. In spite of these facts, polymer solar cells are not covered in current curricula and textbooks of Materials Science and Engineering. The present article intends to provide the remedy to this situation and exhaustively discusses materials, mechanisms and applications in the development of highly efficient polymer solar cells (PSCs).
Keywords: Bulk heterojunction polymer solar cells; Electron acceptors; Electron donors; Inverted and Tandem solar cells; Roll to roll processing; Solar cell efficiency